Penerapan Green Economy pada PT CP: Pembalikan Paradigma dari Ekonomi Eksploitatif ke Ekonomi Konservasi Guna Mewujudkan Pembangunan Berkelanjutan - Urbanus Ura Weruin (Universitas Pahlawan Tuanku Tambusai, 2026)
The green economy represents a shift from a resource-exploitation approach toward a resource-conservation paradigm that balances economic growth with environmental sustainability. Rather than focusing solely on profit and production expansion, this concept emphasizes the need to consider the long-term impacts of economic activities on natural resources and human well-being. Its key principles include efficient resource and energy use, poverty reduction, social equity, renewable energy adoption, low-carbon development, and sustainable consumption and production patterns. The green economy also promotes improved environmental data management and greater awareness of ecological limits. Ultimately, it seeks to enhance quality of life while ensuring the fair distribution of prosperity and the protection of resources for future generations. As a PKM partner operating in the sugar industry, PT CP is closely connected to natural resource utilization and environmental impacts. This program successfully increased the company’s ecological awareness and strengthened its commitment to integrating sustainability into business operations and decision-making processes.